2017
DOI: 10.1002/jso.24936
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma patterns of care in Ontario: A call for a strategic alignment of multidisciplinary care

Abstract: Significant variation exists in melanoma management and nearly one in nine patients is inadequately treated. Referral to sub-specialized providers is critical for ensuring appropriate care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Recent studies have identified that better organization of skin cancer clinical care could benefit Ontario residents. In a paper written by Look Hong et al, it was demonstrated that patients diagnosed with melanoma who only saw a family physician were more likely to receive an inadequate wide local excision of their primary lesion [ 5 ]. In another study, Ontario residents diagnosed with melanoma and who lived in rural communities or long distances from a cancer center were less likely to be seen by a dermatologist within a year before their diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified that better organization of skin cancer clinical care could benefit Ontario residents. In a paper written by Look Hong et al, it was demonstrated that patients diagnosed with melanoma who only saw a family physician were more likely to receive an inadequate wide local excision of their primary lesion [ 5 ]. In another study, Ontario residents diagnosed with melanoma and who lived in rural communities or long distances from a cancer center were less likely to be seen by a dermatologist within a year before their diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the US Surveillance Epidemiology and End Results database for 2004–2006 indicate that 53% of eligible patients received an SLNB,18 while data from a population-based study in the northeast of France indicated that 34% of patients with a melanoma >1 mm in thickness received an SLNB 19. Factors associated with having an SLNB included patient age <50 years,17 primary tumour on upper limb,17 treatment in an urban setting17 19–23 and hospital size (>50 beds) 24. Recent international data indicate that rates of SLNB are increasing: in the Netherlands, the SLNB rate increased from 39.0% in 2003 to 47.8% in 2014 25.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the recent article entitled “Melanoma patterns of care in Ontario: a call for strategic alignment of multidisciplinary care” by Look Hong NJ et al…”
mentioning
confidence: 99%